A revision of the genus Cheliplana de Beauchamp, 1927 (Rhabdocoela: Schizorhynchia), with the description of six new species - Gobert, Stefan; Diez, Yander L.; Monnens, Marlies; Reygel, Patrick; Steenkiste, Niels W. L. Van; Leander, Brian S.; Artois, Tom (Zootaxa, 2021)
A comprehensive morphological and taxonomic account of the members of the genus Cheliplana de Beauchamp, 1927 is presented. Six new species are described: Cheliplana asinaraensis n. sp., C. cubana n. sp., C. curacaoensis n. sp., C. hawaiiensis n. sp., C. longissima n. sp. and C. mauii n. sp. The new species are mainly distinguished from each other and from other representatives of Cheliplana by the organisation of the reproductive system and the structure of the cirrus. Furthermore, C. triductibus Van Steenkiste, Volonterio, Schockaert & Artois, 2008 is considered a junior synonym of Cheliplana deverticula Ax, 2008. The two subspecies of Cheliplana asica Marcus, 1952, C. asica asica and C. asica terminalis Brunet, 1968, are considered separate species. The systematic position of the genus Dactyloplana Armonies, 2018 is discussed, and its synonymy with Cheliplana is retained. As such, this brings the total number of species of Cheliplana to 49. Finally, we provide an identification key to the members of the genus, based on characters that enable identification to species level in the field.